The Role of Non-coding Genome in Cancer-associated Fibroblasts; Stateof- the-Art and Perspectives in Cancer Targeted Therapy - Shabgah, Arezoo G.; Mohammadi, Hamed; Goleij, Pouya; Hedayati-Moghadam, Mahdiyeh; Salmaninejad, Arash; Navashenaq, Jamshid G. (Current Drug Targets, 2021)
Cancer-associated fibroblasts (CAFs) are senescent fibroblasts in tumor nest, which trigger a signaling center to remodel a desmoplastic tumor niche. CAF’s functions in cancer are closely similar to myofibroblasts during the wound healing process. They can produce cytokines, enzymes, and protein- or RNA-containing exosomes to alter the function of surrounding cells. Non– coding RNAs, including microRNAs and long non-coding RNAs, modulate pathologic mechanisms in cancer. Dysregulation of these RNAs influences the formation and function of CAFs. Furthermore, it has been demonstrated that CAFs, by releasing non-coding RNAs-containing exosomes, affect the tumor cells’ behavior. CAFs also secrete mediators such as chemokines to alter the expression of non-coding RNAs in the tumor microenvironment. This study aimed to discuss the role of non-coding RNAs in CAF development in cancer. Additionally, we have shed light on the therapeutic approaches to develop the strategies based on the alteration of non-coding RNAs in cancer.
Keywords: cancer